(untitled) (Medical Forum Monthly, 2024)
Objective: To report our clinical experience of the effectiveness and safety of applying B-lynch suture for the management of primary postpartum haemorrhage. Study Design: An observational, cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology at Peoples Medical College Hospital Nawabshah from 1st January 2009 to 30th June 2010 Materials and Methods: All the patients of primary postpartum haemorrhage in whom compression and conventional ecobolic had failed to achieve uterine contraction and haemostasis were subjected to B-lynch suture. Results: B-lynch suture technique was applied in 33 patients, in 22 patients after vaginal delivery and in 11 patients at the time of cesarean section. This technique was successful in 31 (93.94 %) patients and failed in only 2 (6.1 %). Patients who were proceeded to hysterectomy, none of the patient had infection. Conclusion: B-lynch suture compresses and envelopes the uterus and manages massive life threatening postpartum haemorrhage successfully. It is effective, simple and fertility conserving procedure.